1992
DOI: 10.1093/bja/68.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hypoxaemia After Major Abdominal Vascular Surgery

Abstract: We have studied the severity and duration of nocturnal hypoxaemia before operation and for the first five nights after operation after elective major abdominal vascular surgery. Oxygen supplementation was almost 100% effective in keeping oxygen saturation greater than 90% during the early postoperative period; however, 50% of patients spent prolonged periods with an SpO2 less than 85% during at least one night after operation. The risk of severe hypoxaemia persists well beyond the current prescription of suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 0 publications
6
24
1
2
Order By: Relevance
“…In the postoperative period during the observation of ICU patients, myocardial infarction was diagnosed in three patients (5%): one from group A and two from group B. Although some authors have reported that epidural anaesthesia reduced the risk of myocardial hypoxia [8,16], the majority have not confirmed such effects [4,6,12,17], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the postoperative period during the observation of ICU patients, myocardial infarction was diagnosed in three patients (5%): one from group A and two from group B. Although some authors have reported that epidural anaesthesia reduced the risk of myocardial hypoxia [8,16], the majority have not confirmed such effects [4,6,12,17], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Based on a study in PACU patients, Moller [18] evaluated the incidence of desaturation events and their severity and noted that postoperative hypoxia is a common phenomenon and that oxygen therapy does not protect against hypoxaemia events, which was consistent with the conclusions that were reported by Rosenberg [13] and Russell [12]. Similarly, episodes of hypoxaemia in our study group were common and comprised 90% of patients in both groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…2~ The respiratory depressant effects of opioid analgesia also have an important role in the production of postoperative hypoxaemia. 17 Previous clinical reports have also shown that parenteral morphine results in greater, and clinically important, respiratory depression than equi-analgesic doses of parenteral tramadol. 8.9 The absence of respiratory depression following epidural or parenteral tramadol compared with epidural or parenteral morphine may be attributed to the different mechanisms of their analgesic actions.…”
Section: Discussionmentioning
confidence: 98%
“…Apesar da administração de oxigênio, talvez a metade de todos os pacientes admitidos em unidades de recuperação pós-anestésica tenha diminuição na saturação de oxigênio através da oximetria, em valores de 90% ou mais. A diminuição na concentração arterial de oxigênio pode acontecer particularmente entre o segundo e o quinto dia pós-operatório 64 , pois neste período a suplementação de oxigênio geralmente é descontinuada, sendo porém necessária ainda a administração de opióides para controlar a dor 65 . O uso de analgesia controlada pelo paciente tanto venosa quanto peridural atua de maneira mais consistente, reduz a sonolência, pois diminui a sobredose, porém pode produzir depressão respiratória em idosos mais frágeis 66 .…”
Section: Mortalidade E Morbidade Pulmonar Pós-operatóriaunclassified